IDEOLOGICAL AND ARTISTIC PECULIARITIES OF V. CHUBATYI ‘S MELODRAMA “VOSKRESENNIA” - Rodchyn, Z. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article focuses on research related to dramatic genre – melodrama. Artistic originality of V. Chubatyi’s play “VOSKRESENNIA” in the context of literature process of 20-th – 30-th years of the XX-th century peculiarities is analysed. Special attention is paid to sign attributes of melodrama.